MS ISO 9001 2015 certification improve UMP holistic graduates competitiveness - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PEKAN, 7 October 2022 – Universiti Malaysia Pahang (UMP) is moving towards MS ISO 9001:2015 certification in an effort to produce holistic graduates in line with the university’s aspiration to become the leading technology university.